2019
DOI: 10.1044/2018_ajslp-18-0091
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Language Difficulties in Parkinson's Disease: Caregiver Description and Relationship With Cognition, Activities of Daily Living, and Motor Disability

Abstract: Purpose Parkinson's disease (PD) impacts language in multiple ways, though important questions remain. The current article explores 2 main issues: what type of everyday language difficulties (ELDs) are noted by care partners and how do ELDs relate to cognition, daily activities, and motor disability in PD. Method Care partner reports of ELD were collected in 42 community-dwelling individuals with PD. Descriptive information of ELD was tallied, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In this study, care partners indicated that patients may misrepresent their symptoms during consultations and assessments; at minimum this 'change blindness' is an inevitable consequence of retrospection and introspection. Clinically, the importance of collateral information from care partners of people with PD on activities of daily living [45], everyday language difficulties [46] and psychiatric symptoms [47] is recognised. Nonetheless, some shared with us that they sometimes felt overlooked or inadequately supported, indicating an area for improvement.…”
Section: Other Factors Affecting Trial Retention: the Roles Of Care P...mentioning
confidence: 99%
“…In this study, care partners indicated that patients may misrepresent their symptoms during consultations and assessments; at minimum this 'change blindness' is an inevitable consequence of retrospection and introspection. Clinically, the importance of collateral information from care partners of people with PD on activities of daily living [45], everyday language difficulties [46] and psychiatric symptoms [47] is recognised. Nonetheless, some shared with us that they sometimes felt overlooked or inadequately supported, indicating an area for improvement.…”
Section: Other Factors Affecting Trial Retention: the Roles Of Care P...mentioning
confidence: 99%
“…Moreover, speech deficits are associated with numerous poor outcomes across a range of neurological conditions, including reduced or impaired activities of daily living, greater depression, and poorer quality of life. [83][84][85][86][87][88] Early detection and monitoring of speech may lead to improved outcomes across these domains. In particular, loss of language and communication abilities by patients with MCI and AD is especially challenging for family members.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment involves education regarding ways to optimize swallowing safety with food texture modifications, postural changes when eating or drinking, and exercises including LSVT [152], EMST [153], and chin-tuck against resistance [135,[154][155][156][157]. Speech language pathologists/therapists may play a role in managing drooling, particularly as oral medications to reduce sialorrhea may have adverse effects or contraindications in PD, and also in improving facial expression [12,[158][159][160].…”
Section: Speech and Language Pathology/therapymentioning
confidence: 99%